Preclinical evaluation of Lactiplantibacillus plantarum as a probiotic alternative against multidrug-resistant avian pathogenic Escherichia coli in chickens - El-Sharkawy, Hanem; Abdelsalam, Ahmed Mohamed; Marzok, Mohamed; Hegazy, Yamen; Babiker, Hussein; Tahoun, Amin (Frontiers in Immunology, 2025)
ObjectivesAvian pathogenic Escherichia coli (APEC) is a leading cause of disease and mortality in broiler chickens, resulting in substantial economic losses. Probiotics such as Lactiplantibacillus plantarum (L. plantarum) have shown potential to enhance host immunity and limit pathogen colonization, but their efficacy against APEC is not fully understood.MethodsOne hundred diseased broilers from 20 farms were screened for E. coli isolation, serotyping, and antimicrobial resistance. The probiotic strain L. plantarum ATS1 (GenBank accession no. PV478081.1), previously isolated and partially characterized in our laboratory, was evaluated for adhesion to Caco-2 epithelial cells, survival in murine macrophages, and In Vivo effects on growth performance, serum IgY levels, and protection against oral challenge with APEC O126:K71 at 28 days of age.ResultsTwenty-three E. coli isolates were recovered, with (APEC) predominating (80%) and 20% identified as Shiga toxin-producing O26 strains. Multidrug resistance was common, including complete resistance to cefixime and aztreonam. L. plantarum showed strong adhesion to epithelial cells (5.65 ± 1 bacteria/cell) and survived within macrophages. In Vivo supplementation increased serum IgY, improved body weight gain and feed conversion ratio, reduced cecal and hepatic APEC colonization, and lowered mortality following challenge.ConclusionsL. plantarum ATS1 provides protective and immunomodulatory effects against APEC by supporting intestinal colonization, surviving in macrophages, and enhancing humoral immunity. These findings highlight its potential as a probiotic strategy to improve broiler health and reduce dependence on antibiotics.